Correlation between the number of viable tumor cells and immune cells in the tumor microenvironment in non‐small cell lung cancer after induction therapy. Issue 8 (11th June 2021) - Hoshino, Hironobu; Aokage, Keiju; Miyoshi, Tomohiro; Tane, Kenta; Kojima, Motohiro; Sugano, Masato; Kuwata, Takeshi; Ochiai, Atsushi; Suzuki, Kenji; Tsuboi, Masahiro; Ishii, Genichiro
Abstract: This study aims to determine the correlation between the percent viable tumor cells (%VTC) and the tumor microenvironment in resected non‐small cell lung cancer after induction therapy. We enrolled 72 patients with non‐small cell lung cancer (NSCLC) who received chemoradiotherapy (CRT) or chemotherapy (CT) prior to surgery. The ratio of the area of viable tumor cells to the total tumor area was calculated to obtain the %VTC. We also examined the number of CD4 (+), CD8 (+), CD20 (+) and FOXP3 (+) tumor‐infiltrating lymphocytes (TILs), podoplanin (PDPN) (+) cancer‐associated fibroblasts (CAFs), and CD204 (+) tumor‐associated macrophages (TAMs) by immunohistochemistry (IHC). In the CRT group ( n  = 37), the tumors had significantly lower %VTC than the CT group ( n  = 35) ( P < 0.001). In both of the CT group and CRT group, the %VTC showed a significant positive correlation with the number of CD204 (+)‐TAMs ( P = 0.014 and 0.005, respectively). Only in the CRT group, a higher number of CD204 (+) TAMs was associated with a shorter overall survival (OS) ( P = 0.007) and recurrence‐free survival (RFS) ( P = 0.015). In the CRT group, the number of CD204 (+) TAMs is associated with %VTC and prognosis, suggesting that these cells may have tumor‐promoting effects on the residual lung cancer in specific microenvironments after CRT.